2011
DOI: 10.1175/2010jpo4510.1
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Effects on Intermediate Waters: A Case Study in the East/Japan Sea

Abstract: Although tides are believed to be the most important source for diapycnal mixing in the ocean, few studies have directly simulated open-ocean circulation including tides. Because the East/Japan Sea (EJS) has been considered to be a “miniature ocean,” tidal effects on the intermediate water of the EJS are investigated by using an eddy-resolving ocean general circulation model that can take account of M2 and K1 tides as well as oceanic flows. The simulated temperature and salinity in the intermediate layer are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…This would be the process underlying the two modes of the salinity minimum layer in the southwestern EJS revealed by Cho and Kim []. However, it is still not clear and need to be clarified in the future how the different spatial pattern in NHF in the northern EJS, the frontal mixing/subduction [e.g., Lee et al ., , and tidal effects, e.g., Lee et al ., ] affect the intermediate water properties south of the SF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be the process underlying the two modes of the salinity minimum layer in the southwestern EJS revealed by Cho and Kim []. However, it is still not clear and need to be clarified in the future how the different spatial pattern in NHF in the northern EJS, the frontal mixing/subduction [e.g., Lee et al ., , and tidal effects, e.g., Lee et al ., ] affect the intermediate water properties south of the SF.…”
Section: Resultsmentioning
confidence: 99%
“…One may not rule out the possibility of significant role of largely unraveled mechanisms such as frontal mixing/ subduction [Lee et al, 2006], effects of tidal and near-inertial internal waves [Lee et al, 2011] on the intermediate water formation to a different degree for the two contrasting years, and others. Nevertheless, markedly different circulation patterns in the southwestern part of the EJS (shown below) are most likely to be associated, as a first order, with the differences in intermediate water properties observed off the east coast of Korea.…”
Section: Interannual Variability In Wintertime Surface Heat Flux In Tmentioning
confidence: 99%
“…Most global ocean models neglect tide; internal tides contribute to ocean mixing by propagating through the stratified ocean and eventually breaking down into turbulence [e.g., Alford, 2003;Garrett, 2003]. Models incorporating internal tides may change our understanding of interior ocean circulation, which was demonstrated for the EJS [Lee et al, 2011]. Our result, as a case study in the EJS, provides that spatiotemporal (seasonal) variation of the internal tides due to seasonality of its generation, propagation, and dissipation implies spatiotemporal variation of internal-tide-induced mixing.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Westward-refracting internal waves approaching the east coast of Korea were also detected by satellite images from a synthetic aperture radar [Nam and Park, 2008]. Furthermore, Lee et al [2011] showed meso-scale to large-scale oceanic currents also can be affected by tides. Using numerical simulations, they demonstrated that freely propagating semidiurnal and coastal-trapped diurnal internal tides play a significant role in the formation of intermediate waters in the EJS.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation